Dependence of progeny abundance for fall chum salmon ( Oncorhynchys keta) in the Amur River on the parents abundance - Vladimir I. Ostrovsky; Elena V. Podorozhnyuk; Andrey P. Shmigirilov (Известия ТИНРО, 2015)
The stock of the Amur fall chum salmon ( Oncorhynchys keta ) was low in 2000-2005 (annual catches varied in the range of 500-1300 t) but began to increase since 2006 and the catch exceeded 22000 t in 2014. The increasing was accompanied by gradual decrease of abundance for downstream-migrant juveniles of this species. This opposite effect could be related both with excessive fishing pressure and lack of producers or with excess of the producers number over an optimum, i.e. overloading of spawning grounds - that determines strategy of fishery management. To understand the juveniles lowering, the progeny-parents relationship is considered. It is described by original equation for the difference between the number of spawners and number of progeny. The optimal value of the spawners number is defined as approximately 4.5 · 106 ind. Recently the number of producers regularly exceeds the optimum. So, recent catch values are not excessive, but insufficient, in spite of low number of downstream-migrant juveniles. This conclusion is consistent with conception on harm of spawning grounds overloading for salmons reproduction. Possible consequences of this local stock management on the base of strategy of constant exploitation coefficient and permanent residue are discussed.